Vascularized Palmaris Longus Tendon Graft in Delayed Tendon Injuries of Hand - Handoo, Yog Raj (Indian Journal of Plastic Surgery, 2024)
Delayed tendon injuries of the hand often require auto tendon grafts, the success depending largely on tendon type, its own synovial cover or provided by tendon bed, and tendon bed vascularity. Tendon graft healing has been extensively studied, where tendon does increase its vascular response to trauma, attrition, or degeneration. Initially surviving through synovial fluid imbibition, followed by vascular invasion from surrounding tissues. Tendon grafts without synovial covering or in hypovascular/scarred beds have increased vascular response in the form of flimsy tissue which vascularises tendon grafts but later, they become adhesions, restricting tendon movement and final functional finger results. To overcome this hypovascular state, tendon grafts are substituted with vascularized tendon grafts. We present two cases of vascularized palmaris tendon graft in delayed tendon injuries of hand having hypovascular tendon beds, along with operative technique and results along discussion and conclusion.
Keywords: vascularized tendon graft; vascularized palmaris tendon graft